X-ray irradiation changes germination and biochemical analysis of two genotypes of okra (Hibiscus esculentus L.). Issue 1 (January 2019) - Rezk, Adel A.; Al-Khayri, Jameel M.; Al-Bahrany, Abdulaziz M.; El-Beltagi, Hossam S.; Mohamed, Heba I.
ABSTRACT: The objective of this research was to examine the response of different X-ray doses to two okra genotypes, Hassawi okra and the commercial Clemenson genotype on germination and biochemical analysis. The two genotypes of the okra were subjected to various X-ray doses (0–100 Gy). The findings have been shown that the low doses of X-ray up to 5 Gy caused a significant increase in all morphological criteria, total pigment, enzymatic (ascorbic acid, glutathione, and anthocyanin) and nonenzymatic antioxidants (ascorbate peroxidase, catalase, and superoxide dismutase) in the two okra genotypes as compared with untreated plants. On the other side, the high doses of X-ray above 5 Gy considerably decreased all the above parameters and significantly increased lipid peroxidation and oxidative damage (hydrogen peroxide and superoxide anion) in the two okra genotypes as compared with untreated plants. In conclusion, the low doses of X-ray caused stimulation effect and may be used to improve plant growth and alleviate the stress effects. Okra Hassawi genotype is more sensitive to X-ray than the other genotype.